Temperature Standardization and Quality Standard of Kushta e Gaodanti by Adopting Classical and Modern Methods - Fahamiya, N.; Ansari, S.G.; Ansari, Z.A.; Aslam, M.; Mohammad, Z.; Shiffa, M.S.M. (Journal of Young Pharmacists, 2022)
Kushta Gaodanti (KG) is an essential Unani dosage form prepared by calcination according to classical texts. Standardization is paramount important to check purity and genuineness of the product. However, there are some drawbacks in the calcination process and assessing quality of the drug as per classical method. Hence, this study was aimed to evaluate the quality of KG by classical and modern methods and to develop a quality standard for KG. Methods: A multidisciplinary approach utilizing modern analytical techniques with classical tests was used. Thermogram developed when preparing KG by classical method was used to prepare the drug by Furnace method. The quality of both samples was evaluated on classical parameters like finger test, fineness test, floating test, grain test and wall test and modern physicochemical parameters like bulk density, tapped density, Hausner’s ratio, Carr’s index, pH, Loss on drying, ash values, and extractive values. Characterization using X-ray diffraction, Scanning Electron Microscopy, Energy Dispersive X-ray Analysis, Fourier-Transform Infrared spectroscopy, absorption spectroscopy, Zeta size and potential analysis, and heavy metal analysis have also been carried out to establish the quality standard of KG with modern analytical techniques. Results: The results of the tests done for both the preparations are comparable within experimental error when comparing with each other but non-significant differences were observed in certain parameters. Conclusion: The hysicochemical and analytical parameters evaluated in this study may be considered as standard reference for KG. Furthermore, the thermogram developed in this study can be utilized to prepare the Kushta Gaodanti by the furnace method.
Keywords: Kushta Gaodanti; Arthralgia; Unani Medicine; Gypsum; Physicochemical.